Seleksi dan Kemajuan Genetik pada Generasi F1 Tanaman Kacang Panjang - Nyimas Sa’diyah (Jurnal Penelitian Pertanian Terapan, 2013)
The use of improved varieties is one determinant to obtain high production. Varieties assembly can be done through plant breeding program. One step in plant breeding is the selection. Selection in this study was done by comparing the results of crosses with parental. Of which were selected from crosses can be predicted genetic progress on the next generation. Genetic progress is one of the parameters determining the effectiveness of genetic selection. The experiments were conducted at Integrated Field Laboratory Faculty of Agriculture, University of Lampung Bandar Lampung. The experiments were conducted from November 2011 to April 2012. The main materials used, the F1 seed beans which is a hybrid between the Red and White x Black testa (AxB), testa Black x Red and White (BXA), testa Black x Brown (BxC), testa Brown x Red and White (CXA), Red and White parental seed testa (A), testa Black (B), and testa Brown (C). Treatment arranged in a randomized group design Perfect with 3 replications. Observed variables are: age flowering (HST), the age old harvest pods (HST), number of pods per plant lokul average distance (cm), total seed number, pod shape, and color pods. To form pods and pod color no statistical analysis. The results are: (1) the result of crosses that can be continued on the next generation of F1 from crosses A or B x C x A, and (2) genetic progress for variable flowering 0.7% (low), the age old harvest pods 1.38% (low) number of pods per plant was 52.35% (high) and the number of seeds per plant 43.31% (high). Keywords: selection, genetic progress, F1 generation, cowpea